2010
DOI: 10.1016/j.bbmt.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

An Age-Dependent Pharmacokinetic Study of Intravenous and Oral Mycophenolate Mofetil in Combination with Tacrolimus for GVHD Prophylaxis in Pediatric Allogeneic Stem Cell Transplantation Recipients

Abstract: Acute graft-versus-host disease (aGVHD) still remains a major limiting factor following allogeneic stem cell transplantation (AlloSCT) in pediatric recipients. Mycophenolate mofetil (MMF), an uncompetitive selective inhibitor of inosine monophosphate dehydrogenase, is a new immunosuppressant agent without major mucosal, hepatic, or renal toxicity compared to other prophylactic aGVHD immunosuppressant drugs. Although there has been an extensive pharmacokinetic (PK) experience with MMF administration following s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…Age-dependent pharmacokinetics has been reported for several drugs, including cisplatin, busulfan, thioguanine, etoposide, lamivudine, and mycophenolate mofetil [161][162][163][164][165][166]. Our studies showed that roscovitine elimination half-life was 14-fold higher in young rats compared to adults.…”
supporting
confidence: 53%
“…Age-dependent pharmacokinetics has been reported for several drugs, including cisplatin, busulfan, thioguanine, etoposide, lamivudine, and mycophenolate mofetil [161][162][163][164][165][166]. Our studies showed that roscovitine elimination half-life was 14-fold higher in young rats compared to adults.…”
supporting
confidence: 53%
“…9 We have previously shown that the use of FK506/MMF has been associated with good tolerability and low overlapping toxicities, and it may be equivalent or superior to standard regimens in preventing aGVHD with the appropriate monitoring. 17,25 Thirdly, faster implementation of growth factors, which were started at day 0 in our study, whereas day þ 21 in the Horn et al study. 9 As sequential administration of GM-CSF/G-CSF post-myeloablative AlloHSCT was safe, and resulted in prompt myeloid engraftment, 19 this can possibly contribute to more sustained engraftment.…”
Section: Discussionmentioning
confidence: 82%
“…19,20 MMF was tapered if patients had ⩽ grade II aGVHD on day +180 and tacrolimus was tapered upon conclusion of the MMF taper. 19,20 aGVHD and chronic GVHD (cGVHD) were graded according to Seattle consensus criteria. 21 Supportive care and infection prophylaxis Sargramostim (250 μg/m 2 /day) was started i.v.…”
Section: Gvhd Prophylaxis and Gradingmentioning
confidence: 99%